دور استراتيجية التدريب في التخطيط للمسار الوظيفي "دراسة ميدانية على العاملين في شركة نسيج اللاذقية" - ديب كندة (Latakia University Journal - Economic and Legal Sciences Series, 2016)
The research aims at identifying the role of training strategy -as an essential function of human resources management- in career planning for the employees in Latakia Textile Company.Due to the importance of planning and career development for employees in the public sector and its role in increasing the efficiency of employees performance and thus organization efficiency. Each plan for developing the career path for employees must be accompanied by a comprehensive plan for human resources, therefore a suitable training strategy for career planning and career development for staff should be considered. The researcher selected a random sample of workers in Latakia Textile Company. Questionnaire were distributed among (307) workers. Through the analysis of the data using the statistical software (SPSS), one of the most important findings of the study was thatthe issue of a career planning in the companystudied is obvious. The relationship between the training strategy and career planning among workers in the company studied is at an acceptable level. The study also reveals that there are multiple barriers to career planning in the companystudied, including the lack of sufficient company management contentment of the role of training strategy in career planning and its importance. Also the rules and regulations prevailing in the company’s operations such as promotions delay and job transfers hinder the career planning process. Beside the technology and its associated variables has a negative influential role in career planning and development process. يهدف البحث إلى التعرف على دور استراتيجية التدريب بوصفها وظيفة أساسية من وظائف إدارة الموارد البشرية في تخطيط المسار الوظيفي للعاملين في شركة نسيج اللاذقية, نظراً لأهمية تخطيط المسار الوظيفي وتنميته للعاملين في القطاع الحكومي في زيادة كفاءة أداء العاملينوكفاءة المنظمة. و يجب أن تترافق وتتوافق كل خطة لتنمية المسار الوظيفي وتطويره للعاملين مع الخطة الشاملة للموارد البشرية, كمايجب الأخذ بعين الاعتبار استراتيجية تدريبية مناسبة لتخطيط المسار الوظيفي للعاملين وتطويره. وقد قامت الباحثة باختيار عينة عشوائية من العاملين في شركة نسيج اللاذقية, و وزعت استبانة على (307) عامل منهم ومن خلال تحليل البيانات باستخدام البرنامج الإحصائي (SPSS)توصلت الباحثة إلى النتائج الآتية: هناك وضوح كبيرلمفهوم تخطيط المسار الوظيفي في الشركة المدروسة، كما أن مستوى العلاقة بين استراتيجية التدريب وتخطيط المسار الوظيفي لدى العاملين في الشركة المدروسة هو مستوى مقبول, كما تبين أن هناك معوقات متعددة لتخطيط المسار الوظيفي في الشركة المدروسة من بينها عدم القناعة الكافية لإدارة الشركة بأهمية استراتيجية التدريب ودوره في تخطيط المسار الوظيفي، كما أن اللوائح والأنظمة السائدة في الشركة كتأخر الترقيات وعمليات النقل الوظيفي تعيق عملية تخطيط المسار الوظيفي. هذا وتلعب التكنولوجيا والمتغيرات المرتبطة بها دوراً سلبياً مؤثراً في عملية تخطيط المسار الوظيفي وتطويره.